Short Communication: Detection of bioactive compounds in essential oil from lemongrass cultivated in Ngantang, Malang, East Java, Indonesia - Endang Sri Hartatie; INDAH PRIHARTINI; WAHYU WIDODO; AHMAD WAHYUDI (Society for Indonesian Biodiversity, 2020)
Abstract. Hartatie ES, Prihartini I, Widodo W, Wahyudi A. 2020. Short Communication: Detection of bioactive compounds in essential oil from lemongrass cultivated in Ngantang, Malang, East Java, Indonesia. Biodiversitas 21: 2821-2825. Lemongrass (Cymbopogon citratus) commonly known as West Indian lemongrass is a member of the Poaceae family and belongs to genus Cymbopogon. It is one of the plants commonly used in fresh form as a spice by the people in Indonesia and widely planted in the yard of the house. Lemongrass contains several bioactive compounds and it might be extracted to obtain essential oils useful for many applications such as flavor and fragrance ingredients, perfumery, cosmetics, food preservation, pharmaceutical. The chemical composition of essentials oil can be variable, according to the genetic diversity, habitat, weather, and cultural treatment. The aim of study was to investigate the bioactive compounds in essential oil from lemongrass stalk and lemongrass leaves which cultivated in Ngantang, Malang, East Java, Indonesia. Detection of bioactive compounds was carried out by gas chromatography-mass spectrometry (GC-MS). The results of study are the main compound in lemongrass essential oil was citral. There is a difference between the citral content of essential oils from lemongrass stalk compared to essential oils from lemongrass leaves, both in quantity and components. The citral (geranial and neral) content of essential oil made from stalk was higher than made from leaves, but the amount of bioactive compounds of essential oils from leaves more than from the stalk.